Quora: A popular platform to promote students' reading comprehension skill - Muliyah, Pipit; Ma'rufah, Desi Wijayanti; Mustangin, Mustangin (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Reading comprehension is a fundamental skill in mastering English. Relying solely on classroom instruction is insufficient for providing students with a comprehensive understanding of English texts. As a result, students must actively cultivate their self-directed learning abilities. It enables them to prioritize and focus on the areas they need to improve. Unfortunately, developing independent learning skills can be challenging without encouragement from teachers and an understanding of what they are learning. Thankfully, technology, such as language learning applications, can help overcome this challenge. This study examines using the Quora language learning application to enhance students' reading comprehension skills in English outside the classroom. Using qualitative research, this study involved 18 economic sharia students taking English for Business subject, and data was collected through a questionnaire and interviews. The findings revealed that Quora helped students improve their reading comprehension skills and supported their independent learning by allowing them to study English anywhere and anytime. As a result, students could take control of their learning and significantly improve their English reading skills.